Reestructuración en el proceso de apoyo para el mejoramiento de la gestión de talento humano en el Registro Civil del cantón Latacunga - Guamani Pallo, Karina Lisbeth (2015)
The present investigation was applied in the Civil Registry of the city of Latacunga in order to implement a model of reorganization of the process of human talent with which to succeed in improving its operational capabilities staff who is immersed in the process of based support in the development of activities. This factor includes the adaptation to its standards, identification with the business and institutional objectives and meeting their needs. For the execution of this project required the personnel are trained in the processes to which they are equally required that these are critical judgment and decision making oriented to continuous improvement in the area who work within the institution….